2014
DOI: 10.18869/acadpub.jhs.2.4.59
|View full text |Cite
|
Sign up to set email alerts
|

Medical Errors Management Before and After Implementation of Accreditation in Hospital

Abstract: Background and purpose:This study aimed to manage medical errors before and after the implementation of accreditation in public, private, and social security hospitals of Mazandaran, Iran. Materials and Methods:This descriptive study has been done in 38 hospitals. Data were collected through documents reviewed relating to 2013 and 2014. The paired t-test and Friedman test were used by statistical software SPSS. Results:Results showed that the most and the least percent of reported errors, before accreditation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 7 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…Consequently, improvement in structure and process performance measures could be expected [ 21 , 83 ]. The impact of accreditation on performance measures was the largest topic ( n = 28) explored in our review [ 8 , 18 , 19 , 28 , 48 , 51 , 54 , 60 , 68 , 79 , 87 , 90 , 96 111 ]. Despite the complexity and cyclicality of accreditation effects on performance measures, about three-fourths ( n = 18) of the analyzed studies showed a positive effect of accreditation on service quality at organizational and departmental levels.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, improvement in structure and process performance measures could be expected [ 21 , 83 ]. The impact of accreditation on performance measures was the largest topic ( n = 28) explored in our review [ 8 , 18 , 19 , 28 , 48 , 51 , 54 , 60 , 68 , 79 , 87 , 90 , 96 111 ]. Despite the complexity and cyclicality of accreditation effects on performance measures, about three-fourths ( n = 18) of the analyzed studies showed a positive effect of accreditation on service quality at organizational and departmental levels.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, one of the most important problem of medical centers that threats the patient health and safety is medication errors. 1,2 These errors commonly occur during administering an intravenous drug, drawing blood, failure to use an appropriate equipment, the care procedures of patients during surgery and performing other procedures. [3][4][5][6][7][8][9] Any avoidable incidences which are occur during the process from medication request to patient monitoring is definition of medication error.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] Any avoidable incidences which are occur during the process from medication request to patient monitoring is definition of medication error. 1,[10][11][12][13][14] The most important effect of medication errors are economic consequences, mortality, increase adverse hospital costs and increase hospitalization time. 13,15,16 Nowadays one of the important factors in care systems is patient safety.…”
Section: Introductionmentioning
confidence: 99%
“…Medication errors are one of the most important threats for patients' safety. It is an old problem of hospitals and medical centers (1,2). Administration of intravenous drugs, failure to use appropriate equipment, drawing blood, and monitoring patients during surgery are the most important reasons for medication errors (3)(4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Administration of intravenous drugs, failure to use appropriate equipment, drawing blood, and monitoring patients during surgery are the most important reasons for medication errors (3)(4)(5)(6)(7)(8)(9). Medication errors can be solved in any environment with patient's admission (1,10). Medication error is any damage, risk, and avoidable incidences occurred during the medication practices in order to monitor the patients (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%